Knowledge, Attitude and Practice of Brucellosis among Farmers Rearing Cattle in Belagavi Taluka - A One Year Cross-sectional Study - Hiremath, Neelakanthayyaswamy I; Kangle, Ranjit; Narasannavar, Ashwini (Journal of Pharmacy Practice and Community Medicine)
Introduction: Brucellosis is a zoonotic disease which is almost invariably transmitted by direct or indirect contact with infected animals or their products. It is also known as “Malta fever”, It is an important human disease in many parts of the world especially in the south and central Asia, Mediterranean countries of Europe, north and east Africa, and America and yet it is often unrecognized and frequently goes unreported. More than 500,000 new cases occur annually with an uneven global distribution. In India, bovine Brucellosis is widespread and in recent time it becomes more prevalent, perhaps, due to increased trade and rapid movement of livestock. Epidemiological evidence reveals that, in India, Brucellosis is recorded in almost all states but the scenario differs between states and is present in different species of animals including cattle, goats, buffalo, yaks, camels, horses, and pig. Objectives: To assess the knowledge, Attitude and practice of Brucellosis among Farmers Rearing Cattle. Materials and Methods: A cross-sectional study conducted in Belagavi Taluka among 400 farmers rearing cattle’s. Data was collected using predesigned pretested structured questionnaire after taking written informed consent. Based on the objective the data was analyzed in SPSS version-20 and expressed as percentage. Results: Majority 93.8% farmers had poor knowledge, 4.4% had average knowledge and 1.8% had good knowledge about brucellosis. 99.5% had positive attitude about brucellosis and 97.5% farmers’ had bad practice and only 2.5% had good practice in rearing cattle. Conclusion: Study revealed that majority of farmer’s had poor knowledge and bad practice but had positive attitude about brucellosis.
Keywords: Knowledge; Attitude; Practice; Brucellosis; Farmers